Relación entre el control interno y la gestión de los inventarios en las empresas ferreteras de la ciudad de Iquitos durante el periodo 2022 - Pinheiro Ayambo, Liz Mireya (2023)
The internal control system is important in companies, especially small and medium-sized companies, because it helps to improve quality, improve processes and reduce development costs. Small businesses must organize to know the actual control status of the goods offered for sale and use internal control to analyze management, accounting and sales issues; In this sense, the objective of this research work is to determine the relationship between internal control and inventory management in the hardware companies of the city of Iquitos during the period 2022. For this, a quantitative, non-experimental methodology was achieved, and of correlational design and we found that there is a direct relationship with the management of inventories in the hardware companies of the city of Iquitos during the 2022 period, and that this relationship is significant and high and specifically is 89%.